If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -22 = 2x + 32 Reorder the terms: -22 + 8x = 2x + 32 Reorder the terms: -22 + 8x = 32 + 2x Solving -22 + 8x = 32 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -22 + 8x + -2x = 32 + 2x + -2x Combine like terms: 8x + -2x = 6x -22 + 6x = 32 + 2x + -2x Combine like terms: 2x + -2x = 0 -22 + 6x = 32 + 0 -22 + 6x = 32 Add '22' to each side of the equation. -22 + 22 + 6x = 32 + 22 Combine like terms: -22 + 22 = 0 0 + 6x = 32 + 22 6x = 32 + 22 Combine like terms: 32 + 22 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 4(m+3)+11=2(3m+6)+13 | | 7-6(2a+3)=42 | | -33(12x)+29(21x)=(73-73)+(-737+98) | | -4j+10=-5j | | -15+m=4 | | -3f=8+f | | 2(6b-3)=-78 | | 3(x+7)=-6x-33 | | -19j-20=-6j-15j+18 | | 18=-2x-7x | | -20=31+3x | | 6b-12b+4c+6d= | | 2(x-5)3x=20 | | x+5x-7x+3-x=48 | | 1-(3y+3)=-8 | | -5q-10=-6q | | 4q-3y=27 | | 19-16-17h=-7-18h | | 1-3y+3=-8 | | -38(15x)+28(24x)=(75-75)+(-608+98) | | 5(3x-4)-3=5(x-2)+37 | | 8k=9+7k | | 10m+4=74mis | | -7-2x=2 | | -8d+6=20-10d+18 | | -9m=9-10m | | 24=8(x+2) | | -x+4+4=13 | | 2x(x-3)=18x^2-7x | | -608+98= | | -3(s+17)=-15 | | 9x-126=2x+49 |